Just in case - Viorst, Judith (Atheneum Books for Young Readers, 2006)
Charlie likes to be ready for anything, imagining that his house could be flooded or a mermaid might kidnap him, but he learns that it is sometimes good to be unprepared. Annotation. Charlie is a boy who is always ready for anything...just in case. What if it's raining very hard -- so hard that rain could come into the house and make the furniture float? Charlie has a plan to keep himself dry...just in case. What if his parents are going out and he gets a babysitter who won't read to him or let him watch TV? Charlie has a plan for making his own fun...just in case. Charlie likes to be ready for anything. But as Charlie is about to find out, sometimes not being ready is even better.